Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Purification of waste-generated biogas mixtures using covalent organic framework's high CO2 Selectivity - Paul, Ratul; Maibam, Ashakiran; Chatterjee, Rupak; Wang, Wenjing; Mukherjee, Triya; Das, Nitumani; Yellappa, Masapogu; Banerjee, Tanmay; Bhaumik, Asim; Venkata Mohan, S.; BabaRao, Ravichandar; Mondal, John (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: CAPTURE; CARBON-DIOXIDE; Efficiency; Energy; Hydrogen; STORAGE